2010
DOI: 10.1073/pnas.1016399107
|View full text |Cite
|
Sign up to set email alerts
|

Postsynaptic GluA1 enables acute retrograde enhancement of presynaptic function to coordinate adaptation to synaptic inactivity

Abstract: Prolonged blockade of AMPA-type glutamate receptors in hippocampal neuron cultures leads to homeostatic enhancements of preand postsynaptic function that appear correlated at individual synapses, suggesting some form of transsynaptic coordination. The respective modifications are important for overall synaptic strength but their interrelationship, dynamics, and molecular underpinnings are unclear. Here we demonstrate that adaptation begins postsynaptically but is ultimately communicated to presynaptic terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
65
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 50 publications
5
65
1
Order By: Relevance
“…We recently found that these slow, adaptive changes enable retrograde communication within minutes once AMPAR blockade is removed. Indeed, relief of inactivity allows Ca 2+ permeation through GluA1 homomers, triggering rapid BDNF signaling back to the presynaptic terminal to elevate release probability that can be interrupted by chelation of postsynaptic Ca 2+ (6). Consistent with this scheme (Fig.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…We recently found that these slow, adaptive changes enable retrograde communication within minutes once AMPAR blockade is removed. Indeed, relief of inactivity allows Ca 2+ permeation through GluA1 homomers, triggering rapid BDNF signaling back to the presynaptic terminal to elevate release probability that can be interrupted by chelation of postsynaptic Ca 2+ (6). Consistent with this scheme (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…By the same token, generation of GluA1 homomers would favor Ca 2+ entry when AMPAR blockade is removed, possibly aiding in the rebound of neuronal activity levels. Both changes can be viewed as adaptive to a state of reduced neurotransmission; together, the changes help explain how retrograde transmission can be set in motion by spontaneous minis alone (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are similar to mammalian studies. 24,27,28 These results suggest the existence of presynaptic changes following inactivity that lead to a higher vesicle release probability. Thus, it is possible that decreased Ca 2+ influx during synaptic blockade, or perhaps increased Ca 2+ influx immediately following synaptic blockade may contribute to retrograde signaling to pre-synaptic terminals.…”
mentioning
confidence: 59%
“…It is interesting that GluA2 lacking AMPA receptors, which are Ca 2+ permeable (Cp-AMPARs), have also been shown to play an important role in glutamatergic homeostatic plasticity. [24][25][26] Studies have shown that blocking AMPARs induces increased surface expression of both Ca 2+ -impermeable (Ci) and Cp-AMPARs. Ca 2+ permeable receptors, such as α7 nAChRs or Cp-AMPARs, likely mediate Ca 2+ -dependent pathways involved in homeostasis, regulation of homeostasis, and/or additional forms of plasticity.…”
Section: Intrinsic Plasticity and Roles In Synaptic Homeostasismentioning
confidence: 99%